Inscriptions of political consciousness in childhood memory in Wole Soyinka's 'Ake: the years of childhood' - Javangwe, Tasiyana D. (2016)
This article seeks to interrogate the contradictions that destabilise the apparently innocent representation of childhood memory in Wole Soyinka's Ake: the years of childhood (1981). It seeks to argue that the voice and consciousness of the adult narrator of the here and now intrudes into the memory of the child of the past so as to reformulate childhood experience in ways that propagate desired images/identities of the adult narrator. In this way childhood experience is laden with subtle political and ideological nuances that allow for complex interpretations of the lived subjectivities of both the child subject and those around him. Thus, in the final analysis, the paper seeks to glean instances of political inscriptions onto childhood memory by the adult narrator.